The clinical features and 18F-FDG-PET analysis of absence status epilepsy - Zuo, Jing-Wen; Shao, Xiao-Qiu; Wang, Qun; Lv, Rui-Juan (Frontiers in Neurology, 2025)
Objective To summarize the clinical features and 18F-fluorodeoxy-glucose positron emission tomography (18F-FDG-PET) patterns of absence status epilepsy (ASE). Methods In our study, three patients with ASE were presented, and a comprehensive review of the relevant literature was conducted to elucidate the clinical features and PET results of patients with ASE. Results Seventeen cases of ASE from 7 articles were identified. A total of 20 cases were included in this study, including 9 males (9/20) and 11 females (11/20). The average age at onset was 28.1 ± 15.07 years. Patients with ASE typically present with prolonged episodes of confusion and unresponsiveness. Some patients also present with generalized tonic clonic seizure (GTCS). The episodic frequency was relatively low, ranging from once per year to once per month, and the duration of each episode varied from 30 min to 3 weeks. The episodes of five patients coincided with menstruation, and one patient experienced episodes triggered by sleep deprivation and emotional disturbance. Ictal electroencephalogram (EEG) revealed generalized spike–wave (SW) activity at 2–4 Hz, and brain magnetic resonance imaging (MRI) revealed normal findings. Two patients underwent ictal 18F-FDG-PET, which revealed hypermetabolism in the bilateral thalamus and cerebellar vermis, along with hypometabolism in the bilateral frontal and parietal cortices and cerebellar hemispheres. The three patients in this study underwent interictal 18F-FDG-PET, which revealed decreased metabolic activity in the temporal, parietal, and occipital cortices and cerebellum. Furthermore, the patients’ thalamic area and standard uptake value (SUVavg) were lower than those of healthy individuals. Seventeen cases (17/20) became seizure-free after treatment with valproate (VPA) and lamotrigine (LTG). Interpretation ASE can be considered a specific syndrome of genetic generalized epilepsies (GGEs). Interictal brain PET imaging may reveal relative hypometabolism in posterior regions, along with decreased thalamic area and metabolic activity, potentially indicating the key role of posterior regions in sustaining wakefulness. Most patients responded well to VPA and LTG.